FACTORS INFLUENCING HOMEBUYERS’ DECISION-MAKING IN THE RESIDENTIAL REAL ESTATE MARKET - Gaikwad, Deepesh Deelip; Bhalerao, Amol (International Journal of Research -GRANTHAALAYAH, 2025)
The decision to purchase a house is one of the most important financial and emotional decisions an individual may ever make, determined by a complex interplay among personal preferences, economic factors, and external market forces. This research attempts to identify the key factors that affect homebuyers’ decisions in residential real estate, focusing on location, price and affordability, amenities and infrastructure, builder reputation, financing and interest rates, property size and layout, and socio-psychological motives such as lifestyle aspirations and family needs. Given the rapid urbanization, high disposable income, and fierce competition in the field of real estate in India and elsewhere, understanding buyer preferences has become increasingly vital to developers, marketers, and policymakers in the industry. The research approach will be quantitative, where a structured Google Form survey will be used to collect responses from a diverse group of prospective and currently active homeowners. It is expected that the outcome should emphasize the principal drivers underlying residential purchasing behavior and provide valuable insights that can help developers enhance their product offerings, improve marketing, and help homebuyers make better decisions. This research is practically important to players in the real estate industry as they respond to a changing and highly competitive housing market.